Selection design phase II trial of high dosages of tamoxifen and creatine in amyotrophic lateral sclerosis. Issue 1 (2nd January 2020) - Babu, Suma; Macklin, Eric A.; Jackson, Katherine E.; Simpson, Elizabeth; Mahoney, Katy; Yu, Hong; Walker, Jason; Simmons, Zachary; David, William S.; Barkhaus, Paul E.; Simionescu, Laura; Dimachkie, Mazen M.; et al.
Abstract: Objective : To conduct a phase-II trial using a ranking and selection paradigm where multiple treatments are compared with limited sample size and the best is chosen for a subsequent efficacy trial versus placebo. This strategy can find an effective treatment faster than traditional strategy of conducting larger trials against placebo. Methods : Sixty amyotrophic lateral sclerosis (ALS) participants were randomized 1:1:1 to creatine 30 g/day (CRE), tamoxifen 40 mg/day (T40), or tamoxifen 80 mg/day (T80), with matching placebo. The primary outcome was 38-week change in ALS Functional Rating Scale-Revised (ALSFRS-R), analyzed in a repeated-measures ANOVA. Secondary outcomes included slow vital capacity (SVC), quantitative muscle strength, early drug discontinuation (EDD), adverse events (AEs), and survival. Results : CRE participants experienced higher rates of drug-related AEs (82% vs. 43% T40, 47% T80) and EDD (50% vs. 24% T40, 29% T80). T80 participants experienced slower adjusted mean decline in ALSFRS-R in points/month (–0.80 vs. –0.84 T40, –0.85 CRE) and quantitative muscle strength but not in SVC and higher rates of mortality. Conclusion : Efficacy of T80 ranked numerically superior to CRE and T40 with respect to ALSFRS-R decline. Following the selection paradigm, T80 would be chosen to test against placebo. The approach was not designed to distinguish among treatments that are nearly equally effective or ineffective. If treatments are equivalent, then under the paradigm, it does not matter which treatment is selected. Newer approaches for increasing trial efficiency, including an adaptive platform trial design, may mitigate limitations of the selection design.